Gold and carbene relay catalytic enantioselective cycloisomerization/cyclization reactions of ynamides and enals - Zhou, Liejin (2020)
The combined use of gold as transition metal catalyst and N-heterocyclic carbene (NHC) as organic catalyst in the same solution for relay catalytic reactions was disclosed. The ynamide substrate was activated by gold catalyst to form unsaturated ketimine intermediate that subsequently reacted with the enals (via azolium enolate intermediate generated with NHC) effectively to form bicyclic lactam products with excellent diastereo- and enantio-selectivities. The gold and NHC coordination and dissociation can be dynamic and tunable events, and thus allow the co-existence of both active metal and carbene organic catalysts in appreciable concentrations, for the dual catalytic reaction to proceed.